About myths and true story of Muslims of Ust-Ishim district of Omsk region (Islam through the prism of local history) - A. P. Yarkov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the fight against historical myth-making. The reason for writing the material is the «world discovery» — the time when the Ashevan yurts appeared in the taiga Irtysh region. This became known to «all knowing Wikipedia», indicating the year 1226. A «more modest» date (1296) was mentioned in August 2020 in the Muslim-info newspaper published in Tyumen. The purpose of this article is to refute these historical myths on the basis of scientific and historical facts of the history of Muslims of the Ust-Ishim district of the Omsk region. The author comes to the conclusion that the legend of the birth of the Ashevan yurts in 1226 bears little resemblance to the true «biography» of the village. The described case testifies that in the future, the creation of scientifically grounded «Histories of Siberian villages» is an urgent task for scientists and local historians